Higher neck strength is associated with lower head acceleration during purposeful heading in soccer: A systematic review - Peek, K.; Elliott, J. M.; Orr, R. (Journal of Science and Medicine in Sport, 2020)
Objective: To systematically review the literature to investigate the potential relationship between neck strength and head acceleration during purposeful heading in soccer. Design: Systematic review. Methods: Comprehensive search of five electronic databases: EMBASE, MEDLINE, CINAHL, SportsDiscus and Web of Science. Studies were included if they reported data on the relationship between neck strength and head impact and/or acceleration during purposeful soccer heading, published in English (or translation available). Results: From an initial search of 1174 potentially eligible papers, five cross-sectional studies met the eligibility criteria for inclusion in this review. Data from cross-sectional studies indicate that higher neck strength is associated with lower head acceleration during purposeful heading in soccer (p = <0.05; r < -0.5). Conclusion: This review provides evidence that higher neck strength may lower head acceleration during purposeful heading in soccer. Further research is required to determine the most effective method to strengthen the neck musculature in soccer players.